Transforming Real-Time Payment Infrastructure with Cloud-Native Architecture - Priyatham Nagaiya Seenu Naidu (Malikussaleh University, Aceh, Indonesia, 2026)
The global financial services sector is undergoing a profound transformation driven by the rapid adoption of digital payment technologies, increasing customer expectations for real-time transactions, and the growing demand for scalable and secure financial infrastructures. Traditional monolithic payment systems often struggle to meet these requirements due to limitations in scalability, operational flexibility, fault tolerance, and integration capabilities. Although cloud-native technologies have emerged as a promising solution for modern payment ecosystems, the scholarly literature has not adequately examined how cloud-native architectural patterns address enterprise integration, performance scalability, resilience, and regulatory compliance challenges in large-scale payment environments. This article presents a systematic analysis of cloud-native payment infrastructure by synthesizing architectural patterns, performance benchmarks, and industry case studies from both developed and emerging digital payment ecosystems. The findings demonstrate that event-driven cloud-native architectures can deliver substantial performance improvements, including a 94% reduction in transaction processing latency from 2,400 milliseconds to 128 milliseconds, near real-time fraud detection with response times of approximately 0.05 seconds, and fraud identification performance achieving 99% recall and 83% precision through hybrid deep learning models. Furthermore, production-scale validation is evidenced by successful implementations such as India’s Unified Payments Interface (UPI), which processes over 10 billion transactions monthly, and Brazil’s PIX platform, capable of handling up to 200,000 transactions per second. Security and compliance analyses reveal that immutable event-sourcing mechanisms, combined with comprehensive audit trails and encryption strategies, facilitate adherence to major regulatory frameworks, including PCI-DSS, GDPR, and anti-money laundering requirements. However, significant implementation challenges remain, particularly concerning legacy system integration, cross-jurisdictional regulatory fragmentation, organizational transformation, and shortages of cloud-native engineering expertise. Based on these findings, practical implementation guidelines emphasize microservice-based architectures, end-to-end event-driven processing, and zero-trust security principles. Future research directions include post-quantum cryptographic migration strategies, central bank digital currency interoperability standards, sustainable payment infrastructure design, and the application of artificial intelligence for autonomous financial operations and risk management.